(untitled) (International Journal of Physiotherapy, 2015)
Background: Osteoarthritis is the most common cause of musculoskeletal pain and disability in the knee joint. This study investigated the efficacy of Dextrose iontophoresis versus Dextrose prolotherapy in case of knee osteoarthritis in a randomized, placebo-controlled, double-blinded study. Methods: sixty patients diagnosed mild to moderate osteoarthritis were included in the study. Their age’s were45:65 years with mean age 51 ± 3.5 years. Patients were divided randomly into three equal groups, group (A)received 50 % dextrose iontophoresis, group (B) Each patient received three intra-articular injections of dextrose at 1-month intervals in weeks 0, 4, and 8 and group (C ) received sham iontophoresis. The outcome measurements were Western Ontario and McMaster Universities arthritis index (WOMAC) values, knee ROM, and pain severity at rest (seated) and in activity (after walking 6 m) using the visual analogue scale (VAS) were recorded. The patients were evaluated for these parameters before allocated in their groups then after 4, 8, and 24 weeks later. Results: compared to sham group (placebo) there were significant improvement of VAS and ROM of iontophoresis group than sham (placebo) group (p<0.000). Also there were significant improvement of prolotherapy group than placebo (p<0.006, and 0.02) respectively. Furthermore there was significant improve of iontophoresis group than prolotherapy where p was <0.000 for VAS, ROM and (WOMAC). Conclusion: The results of this study suggested that both dextrose iontophoresis and dextrose prolotherapy may be as useful modalities in treatment of osteoarthritis with better effects of dextrose iontophoresis than prolotherapy.